Harlem Renaissance in the USA - Xusanova Indira Akbardjanovna; Matyokubova Shukurjon Farhodovna (Peerian Journals Publishing, 2022)
To identify dements and reveal the techniques used by the author to illustrate racial discrimination and injustice. This work includes several tasks that will be clarifying: to give general information; to give brief information of the evidence of the Harlem period in America; to explain about that period in America. In this research include historical, biographic, analytical, descriptive and comparative methods.
Keywords: literature; drama; music; dance